Short-term preservation of Pecari tajacu ovarian preantral follicles using phosphate buffered saline (PBS) or powdered coconut water (ACP(r)) media - G.L. Lima (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2014)
We compare protocols for the short-term preservation of collared peccarie's ovarian preantral follicles (PFs) by using phosphate buffered saline- (PBS) or powdered coconut water- (ACP(r)) based medium. For morphology analysis each pair of ovaries collected from six females was divided into nine fragments. One fragment was destined for morphology analysis (histology and transmission electron microscopy - TEM), constituting the control group and the other fragments were placed in tubes with PBS or ACP(r), packed in 5 L Styrofoam boxes, stored for 4h, 12h, 24h, and 36h, and then analyzed. For viability analysis a pair of ovaries from two additional females was divided into nine fragments; one fragment was immediately destined for viability analysis (Trypan blue test) and the other fragments were stored as previously described, until 24h and then analyzed. After 4h storage in ACP(r) medium, the follicular integrity was similar to control (87.8% vs 94.4%, respectively); however, ultrastructural analyses revealed swollen mitochondria as the first signals of PF degeneration. It was observed that ACP(r) (66.7%) was more efficient than PBS (49.4%) to preserve the morphological integrity after 36h storage (P<0.05); however, no differences were observed on follicular viability (P>0.05). In conclusion, the use of the ACP(r) is recommended for the short-term preservation of Pecari tajacu preantral follicles.